The obstacle race: the fortunes of women painters and their work - Greer, Germaine (Farrar, Straus, Giroux, 1979)
If men and women are equally capable of genius, why have there been no female artists of the stature of Leonardo, Titian or Poussin? In seeking to answer this question, Germaine Greer introduces us to major but underestimated figures in the history of Western painting–Angelica Kauffmann, Natalia Goncharova, Suzanne Valadon, Berthe Morisot, Kathe Köllwitz–and produces a brilliantly incisive and richly illustrated study. She explains the obstacles as both external and surmountable and internal and insurmountable in the race for achievement.
Section: 373 pages
Keywords: 1900-1999; amérique du nord; amériques; approches et analyses; arts; cours; discipline; discours dominant; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; périodes historiques; régions; régions géographiques; sexisme; systèmes d'oppressions; thématiques; théorie de l'art

Féminisme et socialisme aux États-Unis : textes du parti socialiste des travailleurs - Le Calvez, Françoise; Socialist Workers Party (USA) (‎Union Générale d'Editions, 1979)
Choix de treize textes parus dans les années 1970. La perspective est celle de la libération des femmes et de la lutte contre leur oppression et contre le capitalisme et la bourgeoisie. Deux des textes inclus ont paru séparément en anglais.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cours; fem1000; patriarcat; premier cycle; périodes historiques; régions géographiques; socialisme; systèmes d'oppressions; états-unis

Le monde de la chanson. Comment quatre femmes ont pris place dans l'industrie du disque - Lemay, Jacqueline (Canadian Woman Studies, 1979)
Keywords: 1900-1999; 1970-1979; DIG; amériques; arts; chanson; discipline; musique; périodes historiques; québec; ressource en ligne; régions géographiques; sororité; thématiques; travail

Originals: American women artists - Munro, Eleanor C. (Simon and Schuster, 1979)
Discusses the lives and work of Mary Cassatt, Georgia O'Keefe, Alice Neel, Louise Nevelson, Helen Frankenthaler, Elaine de Kooning, Sylvia Stone, and other American women artists
Keywords: 1900-1999; Biography; amériques; arts; biographie; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Les Services sociaux vs les lesbiennes et les gais du Québec : un dossier noir - Rassemblement national des lesbiennes et gais du Québec. (Le RNLGQ, 1979)
Keywords: 1900-1999; 1970-1979; amériques; corps; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; québec; régions géographiques; santé; thématiques; violences

Les femmes : caste, classe ou sexe opprimé - Reed, Evelyn (Féminisme et socialisme aux États-Unis. Textes du Parti socialiste des travailleurs, 1979)
Keywords: 1900-1999; amériques; antiracisme; approches et analyses; classe sociale; cours; fem1000; histoire et politique; militance; mouvements des femmes*; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis